مكانة الرّسول- صلى الله عليه وسلم- في نبويّات الشّاعر مصطفى يوسف التّني - إسماعيل أمبدة, ود أمبدة عمار عبد الرحمن (جامعة الوادي university of eloued, 2023)
لخص: تناولت هذه الدّراسة مكانة الرّسول- صلى الله عليه وسلم- في نبويّات الشّاعر مصطفى يوسف التّني، وهي القصائد التي نظمها في مدح النبي الكريم عليه الصلاة والسلام، وهدفت إلى أنّ الشّاعر التّني استطاع أن ينسج بنفس عربي حديث، عواطفه الإسلاميّة ومشاعره الدّينيّة الصّادقة في تصوير شخصيّة رسول الله- صلى الله عليه وسلم- مدحاً ووصفاً واستنجاداً واستعطافاً ومحبةً. ومن ثمّ الوقوف على مكارم أخلاقه المتمثّلة في: الرّحمة والعطف، والكرم والجود، والصّحبة الصّالحة، والدّعوة إلى طريق الهدى، وكذلك الوقوف على الدّراسة الفنيّة كالمنحى الفني والأسلوبي، والصّورة الشّعريّة ووحدة القصيدة. اتّبعت الدّراسة المنهج الوصفي الاستقرائي. وخلصت الدّراسة إلى عدد من النّتائج من حيث مجملها: أعطى التّني الرّسول- صلى الله عليه وسلم- مكانته التّي وضعها الله عزّ وجل فيها، فهو في نبويّاته يفوق سائر الخلق والأنبياء جميعاً في خلقه وعمله فكلهم يقتبس من كماله فهو سر كل وجود وأصل كل شيء، وهو المنبع بكلّ خلق كريم وكلّ علم إلهي وهم يقفون منه عند حدّ لا يتعدّونه فقد استمدّوا الخلق الرّفيع والعلم والحكمة من نوره. توصي الدّراسة بمزيدٍ من الدّراسات في مدح رسول الله- صلى الله عليه وسلم- في الشّعر السّوداني. الكلمة المفتاحية: نبويّات؛ الشّاعر؛ التّني؛ مكانة؛ الرّسول. Abstract: This study dealt with the status of the Messenger - may God bless him and grant him peace - in the prophecies of the poet Mustafa Yusuf al-Tani, which are the poems he composed in praise of the Holy Prophet, peace and blessings be upon him. Depicting the personality of the Messenger of God - may God bless him and grant him peace - praising, describing, pleading, pleading and loving. And then standing on the honorable morals represented in; Compassion and kindness, generosity and generosity, good company, and the call to the path of guidance, as well as standing on artistic study such as the artistic and stylistic approach, the poetic image and the unity of the poem. The study followed the inductive descriptive method. The study concluded a number of results as a whole; The dragon gave the Messenger - may God bless him and grant him peace - his place that God Almighty placed in it, so in his prophethood he surpasses all creation and all prophets in his creation and work, so they all quote from his perfection, for he is the secret of all existence and the origin of everything, and he is the source of every generous creation and every divine knowledge while they stand From Him there is a limit that they do not transgress, for they have derived lofty morals, knowledge and wisdom from His light. The study recommends further studies in praising the Messenger of God - may God bless him and grant him peace - in Sudanese poetry. Keywords: prophetic; Poet; figment status; Prophet
مقال
Keywords: يات الشاعر التني مكانة الرسو ل.